Analysis of the participation of transnational corporations in development strategies in Latin America and Asia. The cases of South Korea and Brazil - Pérez Lagüela, Elena (Papeles de Europa, 2021)
This article aims to systematise the causes that determine the different results of the development processes in two regions, Latin America and East Asia, which undertook similar developmental strategies with different outcomes. To this end, the role that transnational companies have historically played in development strategies in both regions will be studied, using as case studies two representative countries, both for the implementation of development policies and for the contribution of transnational corporations to those processes: Brazil and South Korea. Thus, an attempt will be made to determine to what extent the participation of transnational corporations has been decisive in the success of development strategies in both countries.